2017
DOI: 10.1038/srep41718
|View full text |Cite
|
Sign up to set email alerts
|

MFN2 suppresses cancer progression through inhibition of mTORC2/Akt signaling

Abstract: The mitochondrial GTPase mitofusin-2 (MFN2) has previously been reported to play a role in regulating cell proliferation, apoptosis and differentiation in a number of cell types. Here, we report that breast cancer patients with low MFN2 expression are associated with poor prognosis as compared to patients with high MFN2 expression. We find that MFN2 knockout from MCF7 and A549 cells via Crispr/Cas9 greatly promotes cell viability, colony formation, and invasion of cancer cells in vitro and in vivo, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 35 publications
(34 reference statements)
7
86
0
Order By: Relevance
“…Akt plays a major role in regulating ER and mitochondrial apoptosis pathways. 24,25) In this study, phosphor-Akt was significantly increased by bavachin in a time-dependent manner, while total Akt have no apparent change (Figs. 5A, B).…”
Section: Effect Of Bavachin On Viability In Hepg2 Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…Akt plays a major role in regulating ER and mitochondrial apoptosis pathways. 24,25) In this study, phosphor-Akt was significantly increased by bavachin in a time-dependent manner, while total Akt have no apparent change (Figs. 5A, B).…”
Section: Effect Of Bavachin On Viability In Hepg2 Cellsmentioning
confidence: 90%
“…[54][55][56] A recent study suggested that the overexpression of Mfn2 suppressed cancer progression through inhibition of Akt signaling. 24) Furthermore, bavachin was reported to exhibit direct effect on Akt phosphorylation. 11,57) In this study, we showed that Mfn2 ablation by the siRNA resulted in the inhibition of phosphor-Akt, and inhibition of phosphorAkt also aggravated bavachin-induced ER stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins involved in regulation of mitochondrial dynamics are now identified as important biomarkers of malignancy, including therapeutic targets in several tumor types (21). Thus, the enhancement of mitochondrial fragmentation by attenuating MFN2 has been associated with increased genomic instability and reduced migration and invasion in breast cancer cell lines, which predominantly exhibit fused mitochondrial morphology (47,48). Impaired mitochondrial fusion also causes aberrant mitochondrial function, characterized by acquired mitochondrial DNA mutations and ROS production (36).…”
Section: Discussionmentioning
confidence: 99%
“…As for cell growth, mitochondrial fusion seems to oppose fission and inhibits invasiveness of both breast and lung cancers (Xu et al, 2017). Low expression of MFN2 for patients of both diseases correlates with poor prognosis.…”
Section: Cancer Cell Migrationmentioning
confidence: 99%